Social media, traditional media and party politics in Ghana - Gyampo, R.E.V. (My University, 2017)
The social and political context within which political parties operate has significantly changed in the twenty-first century. The global breakthrough in social media offers numerous possibilities for meaningful and equal participation, as well as chances for new forms of transparency and accountability, in ways that were until recently, unimaginable. This study identifies and discusses the specific ways in which political parties in Ghana have deployed social media in advancing their interest. It raises the challenges that have been encountered by political parties in their quest to tap the advantages of social media in prosecuting their ultimate agenda of capturing political power. It argues succinctly that even though social media has broad advantages, it has severe challenges that undermines its effectiveness and nullifies any attempt to use it as a substitute to traditional media in Ghana. The study recommends an improved use of traditional media as a means of reaching out to people by political parties, as well as the use of social media only as an ‘additional communication luxury’.
Keywords: Political parties; social media; Facebook; communication; internet